Model Of Arival/Departure And Charge/Discharge Management In Port Zone Using Petri Net. - AL-eraqi, Ahmad Salem; Tajudin, Assoc.Prof. Ahamad; Mustafa, Adli (2005)
In view of the economic importance of port for the countries, and due to the unique nature of this activities for the international navigation, the tasks that its management should perform optimally have been multiple.